Safety and nature versus tourists, athlets and residents in Sagarmatha National Park Nepal - Brenk, Agnieszka; Smoleńska, Olga Ilona (Quality in Sport, 2020)
The subject of this publication is Sagarmatha National Park located in Nepal, along with the consequences of its popularity among all worlds and the effects of using the environment on selected specific cases. The main purpose of the work is to illustrate the included natural and social conditions as well as the state and perspectives for the development of operational functions in the park. The economic situation of the country will also be presented, taking into account the conditions conducive to the development of inbound tourism. High mountains have now become one of the main collections of scientific research. One of the reasons is the intensive transformation available from the mass nature of qualified tourism or mountain climbing. The world has entered the multifaceted era of 'tourism'. The natural values of the environment are currently covered by one of the basic elements of the supply of the harvest. Man cannot be chased from the mountains! It is necessary to include his harmonized sport, tourism and economic interests with nature protection. Tourism supported and contributes to the development of various forms of nature and environmental protection, which are the first national parks and nature reserves: Yellowstone in the USA founded in 1872, the Royal National Park in Australia founded by the British in modern colonies in 1879 or the second historical Banff National Park in Canada created in 1885. Contemporary forms of environmental protection originate from the romantic west over wild nature and associated with progressive industrialization in the nineteenth century destroying natural ecosystems on an unprecedented scale. Although the ideas of nature protection may already be sought in antiquity for activities that will then be related to religious worship. In China, the first laws on nature protection were announced 4,000 years ago, and in India about 3,000 years ago. The declaration on the protection of forest resources was issued in 1671 by the Danish King Christian V, and 34 years later also by Russian Tsar Peter I. In Poland, the first symptoms of care for forest resources concern the place in 1337, during the reign of Casimir the Great, when he announced statutes prohibiting logging in other people's forests. Conscious protection of the disappearing species in the form of royal law takes place at the end of the 16th century, which provisions protect the forced turns as a result of cutting out large tracts of forests. In Nepal, ecological awareness of the power elites and local people has matured for a long time. Robbery of forest management was widely used, wood for fuel or land was obtained for arable crops. It wasn't until the mid-1960s that King Mahendra issued the first laws on nature protection and provided for penalties for its destruction. The descendant and heir to the throne of King Mahendra - Birendra permanently introduced the protection of natural resources to the country's development plans and in the first year of his reign (1973) he issued the Act on National Parks and Nature Conservation, which took care of a number of animal species and established the first Royal Chitwan National Park. In subsequent years, new national parks and reserves were created in naturally valuable areas. There are 8 national parks in Nepal. The protected areas cover a total of 13% of the area. The inspiration to write this study was data analysis and own observation of both the natural resources of the Sagarmatha National Park, as well as the attitude to the natural environment of its inhabitants as well as athletes and tourists.